The impact of marching band co-curriculum activities on students’ academic achievement in SMK Sultan Yussuf / Muhamad Hazrin Ishak - Ishak, Muhamad Hazrin (Faculty of Music, 2016)
This study was conduct to examine the impact of marching band co-curriculum activities on students' academic achievement in Sekolah Menengah Kebangsaan Sultan Yussuf. The purpose of this study is to find out the impact of marching band cocurriculum activities on students' academic achievement in Sekolah Menengah Kebangsaan Sultan Yussuf. For this particular study, the data are collected from marching band form two level student's academic achievement databases from SMK Sultan Yussuf, Batu Gajah, Perak, books, article and journal by different authors who talk about impact of music activity towards academic achievement. The data gathered was analysed and based on the three research question.